The yoga healer : remedies for the body, mind, and spirit : from easing back pain and headaches to managing anxiety and finding joy and peace within /: remedies for the body, mind, and spirit : from easing back pain and headaches to managing anxiety and finding joy and peace within. (2017) - (Yoga teacher), Burke, Christine
No abstract available